LAYANAN INFORMASI DALAM MENINGKATKAN KEMAMPUAN ADAPTABILITAS KARIR DI MASA NEW NORMAL - Ismuniar, Cici (LPPM Institut Pendidikan Nusantara Global, 2023)
This research aim to determine the effecitiveness of information services application to improve students career adaptability in the new normal period in class XI of SMK Negeri Tarakan. This research was a pre-experimental design research using one group pretest-posttest with a quantitative approach with a population of class XI students of SMK Negeri Tarakan totaling 108 students and the sample used is Simple Random Sampling totaling 30 students. The research instrument was a career adaptability scale based on Savickas’s theory (2012). Data analysis techniques were descriptive analysis and inferential analysis with Paired Sample T-test hypothesis testing. The Paired Sample T-test test used SPSS 16.0 for windows. The data analysis results of the Paired Sample T-test test obtained a Sig (2-tailed) value of 0.000 < 0.05, so Ho was rejected and Ha was accepted, which means that information services were effective for improving students’ career adaptability during the new normal period in class XI SMK Negeri Tarakan. Based on results of the pretest score obtained by 30 students as a sample of this research, 10 (33%) students had a high level of career adaptability and 20 (67%) students had a moderate level of career adaptability. The results of the posttest score showed that there were 19 (64%) students who had a high level of career adaptability and 11 (36%) students who had a moderate level of career adaptability.